Unemployment, Excess Capacity, and Benefit-Cost Investment Criteria - Haveman, Robert; Krutilla, John (The Review of Economics and Statistics, 1967)
URING the past several years, substantial efforts seeking improvement in the design and economic evaluation of water resource (and other) public investments have been forthcoming.The issue in all of these analyses concerned both the nature of the appropriate investment criterion and the techniques for accurately estimating the parameters and variables which are its constituents.'While all of these contributions acknowledged the inadequacy or absence of market values in evaluating some benefits, generally all accepted the market prices of factors in computing the costs of project construction.2The primary rationale for this position rests on the proposition that, given full employment and factor markets which function as reasonably efficient allocative mechanisms, nominal factor prices reflect real cost and (social) worth.3However, even though most analysts have adopted the full-employment assumption in their own work, all have indicated the desirability of adjusting money costs so as to reflect more adequately true opportunity costs in a severe and widespread depression.4While the rationale for this position has varied among economists, essentially the same information is required to correct market costs, irrespective of viewpoint.For any particular project, knowledge is required of both the direct and indirect industrial and occupational demands imposed on the economy and the correspondence of the pattern of these demands with the pattern of unemployment and idle industrial capacity.Because of the magnitude of the empirical task of tracing these sectoral demands through several layers of transactions, appropriate cost adjustments have not, in practice, been made.Indeed, the impracticality of the empirical task may explain, as much as anything, the failure of the economics profession to choose the problem as a research undertaking.Recently, however, three basic empirical studies have been completed which enable the detailed tracing of public investment demands.In 1964, the Bureau of Labor Statistics released its study of the detailed on-site labor and materials reouirements of water resource